A Review of Learning Organization Concept from Islamic Perspectives - Aini, Ahmad; Hasan, Ahmad (Universiti Malaysia Pahang, 2016)
The paper’s purpose is to explore the concepts and understandings of learning organization from an Islamic perspective. It also aims to examine the potential integration of the learning organization idea in Islamic organization. The study analyses four understandings of learning organization as proposed by Örtenblad (2002) followed by Islamic views for each understandings. The findings suggest that the idea of learning organization is in harmony with Islamic teaching in many ways. Empirical research on the practice of learning organization in Islamic organizations is needed to shed more lights on the subject. Learning organization can be successfully implemented in Islamic organizations and Islamic organizations can be a ‘learning organizations’.